Faktor Risiko Kejadian Preeklamsia Berat (Peb) di Rumah Sakit Umum Daerah 45 Kuningan - Heriana, Cecep; Nurasiah, Ai; Fahmi, Rianur (Jurnal Ilmu Kesehatan Bhakti Husada: Health Sciences Journal, 2013)
Introduction: Maternal death is a major problem in global and developing countries. The Causes of maternal death are preeclampsia, eclampsia and infection. Severe Preeclampsia incidence in Indonesia is 10-13% from all maternal, was improve severe preeclampsia between 2010 and 2011 is 58% in Kuningan Hospital. The purpose study to determine risk factor associated with the incidence of Severe Preeclampsia in Kuningan Hospital between January and December 2011. Methode: The research design used an observational with retrospective cohort study. The sample are mother with one more preeclampsia risk factor in JanuaryDecember 2011 many as 1862 respondents and sample taken by total random sampling. The variable is age, parity, diabetes mellitus, gemelli, and hypertension history. Statistical test used was chi-square and fisher exact (bivariate analysis) and Relative Risk (RR). Result : Result of univariat analysis is 13,2% severe preeclampsia, 43,5% risk age group, 60,3% primigravida, 0,2% Diabetes mellitus,, 3,2% gemelli and 20,2% hypertension history. Bivariate analysis is age p=0,721 (RR 0,96 CI 95% 0,76-1,21), parity p=0,00 (RR 0,33 CI 95% 0,25-0,42), Diabetes mellitus p=0,002 (RR 7,68 CI 95% 6,83-8,64), gemelli p=0,381 (RR 1,3 CI 95% 0,73-2,32) and hypertension history p=0,00 (RR 7,55 CI 95% 5,95-9,58). Discussion: Parity, diabetes mellitus and hypertension history related to severe preeclampsia incidence. Recommendation to Kuningan Hospital to increase monitoring Antenatal Care and counseling to maternal.